Outcomes in BCG failure: Outcome from a single centre UK experience - Elizabeth Day; Rachel Aquilina; Lazaros Tzelves; Ashwin Sridhar; Anthony Ta; John Kelly; Bernadett Szabados (BJUI Compass)
Abstract Objective To describe real‐world outcomes of patients with BCG failure undergoing bladder‐sparing treatments (BSTs) vs radical cystectomy in the UK. Patients and Methods A single institution audit was conducted at a tertiary bladder cancer referral service (UCLH, London, UK). Patients with BCG failure treated between January 2017 and September 2022 were included. BSTs included endoscopic surveillance, hyperthermic mitomycin and further BCG. The primary outcome was event free survival (EFS). Complete response (CR) rate and duration of response (DoR) were investigated in patients undergoing BST. The secondary outcomes were 3‐ and 5‐year cancer‐specific (CSS) and overall survival (OS). Results A total of 112 patients were included: 30% (34/112), 32% (36/112) and 27% (30/112) had BCG unresponsive, exposed and intolerant disease and 11% (12/112) had progressed to muscle invasive disease (MIBC). In the BCG unresponsive and exposed groups, 79% (27/34) and 72% (26/36) underwent RC, with the remaining receiving BSTs. Comparing RC vs BST in BCG unresponsive and exposed groups combined, there was a significantly poorer EFS in the BST group (p < 0.001); 35.3% (6/17) patients transitioned to second‐line BST due to recurrence or intolerance and a further 50% (3/6) transitioned a third line BST. There was no significant difference in CSS or OS rates. In BCG intolerance, the EFS rate was 90% as three patients experienced high‐grade recurrence and underwent RC. There were no cancer‐related deaths. In MIBC group, 5/12 presented with metastatic disease and 3‐ and 5‐year CSS rates was 66% and 0%. Conclusion This data reports real‐world practice in a UK centre. BSTs in BCG unresponsive and exposed disease are supported as an alternative to RC providing the increased risk of recurrence is accepted. Additionally, consideration of formal guidance supporting BST is needed in BCG intolerance, which appears to have an excellent outcome in a cohort managed with endoscopic surveillance. Upstaging to MIBC remains a poor prognostic factor and is key to improving survival outcomes in BCG failure.